2006
DOI: 10.1080/09658210544000042
|View full text |Cite
|
Sign up to set email alerts
|

The role of proactive interference in mnemonic techniques

Abstract: The success of many mnemonic techniques, such as the method of loci, is based on the use of specific well-known anchors, which are mentally combined with to-be-learned items and subsequently facilitate their retrieval. In our studies we intended to answer the question of whether the repeated application of the method of loci may result in proactive interference effects, as might be expected due to the applied association of items with the same loci each time the method is used. To this end, we manipulated list… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In a study of those with superior memories, all used memory strategies, and 90% reported using the MOL (Maguire, Valentine, Wilding, & Kapur, 2003). Memory training studies affirm the strength of this strategy to improve memory performance in both young and older participants (Lustig & Flegal, 2008; Massen & Vaterrodt-Plünnecke, 2006; Nyberg et al., 2003; Rebok & Balcerak, 1989). In our study, participants without instruction in the MOL recalled about 88% of the low interference List 1 and about 50% of the high interference List 5.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…In a study of those with superior memories, all used memory strategies, and 90% reported using the MOL (Maguire, Valentine, Wilding, & Kapur, 2003). Memory training studies affirm the strength of this strategy to improve memory performance in both young and older participants (Lustig & Flegal, 2008; Massen & Vaterrodt-Plünnecke, 2006; Nyberg et al., 2003; Rebok & Balcerak, 1989). In our study, participants without instruction in the MOL recalled about 88% of the low interference List 1 and about 50% of the high interference List 5.…”
Section: Discussionmentioning
confidence: 80%
“…Imagery provides an immediate way to integrate a set of information (Rubin, 1995) and it is well suited for moving quickly from one situation to another (Paivio, 1971, as cited in Rubin, 1995), but it is the loci that hold items in memory and make items more accessible in recall (Massen & Vaterrodt-Plünnecke, 2006; Roediger, 1980). Image appears to function locally to improve recall by accessing only local information at one time in one place (Rubin, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the latter, research indicates that the method of loci indeed enhances serial recall (Ross and Lawrence, 1968;Christen and Bjork, 1976;Wang and Thomas, 2000), even after a substantial retention interval (Groninger, 1971;Wang and Thomas, 2000). Furthermore, research has demonstrated that the same loci can be used to learn several different lists without proactive interference (Christen and Bjork, 1976;de Beni and Cornoldi, 1988;Massen and Vaterrodt-Plunnecke, 2006). Some evidence also suggests that mnemonic training with the method of loci can curb some age-related memory differences in elderly adults (Hill et al, 1991;Brooks et al, 1999).…”
Section: The Methods Of Locimentioning
confidence: 93%